Blogging a Five Element Life. - Franglen, Nora (Jessica Kingsley Publishers, 2017)
The follow-up to Nora Franglen's first book of collected posts on the holistic life of an acupuncturist, this provides further insight into the everyday musings of a master of her craft. From her love of London's cafes to challenges she has experienced in her clinic, it reveals how acupuncture can enrich and balance all aspects of our being.